THE TRUE ESSENCE OF RECLAMATION OF AGRICULTURAL LANDS: MISSION AND DEVELOPMENT TRENDS - Mustafayev Zhumakhan Suleimenovich, (Academic Journal of Physical and Chemical Sciences, 2021)
To identify the reasons for the current situation in the irrigated lands of Central Asia and South Kazakhstan, on the basis of philosophical and methodological reasoning of a general nature, sticking out of a cognitive attitude to the environment on reality and focused on one value, that is, at any cost to get a «record» harvest from agricultural crops, led to an ecological and reclamation crisis in irrigated lands in general, requiring the development of the main directions of activities to improve the human habitat with other natural and bio spheric processes. As a result, for the first time in world practice, irrigation and drainage (collector-drainage) systems were designed in parallel in the zones of insufficient moisture for the regulation and management of hydrological regimes of ground and surface waters in rice systems, despite violating the principles of natural analogy and the integration of knowledge, where the sovereign interests of a person prevailed by sovereign “interests" of Nature. At the same time, world experience shows that the new knowledge gained on irrigation of rice as an aquatic and terrestrial crop, surface irrigation along the furrow, sprinkler irrigation and drip irrigation systems in combination with doses of macro fertilizers, made it possible to formulate a scientific hypothesis of cost-effective and environmentally safe management of the water regime providing targeted regulation of the soil-forming process.